Identification of Broadleaf Weeds in Citrus - Stephen H. Futch; David W. Hall (EDIS)
This document is HS-896, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published February 2003.